2014
DOI: 10.1080/15421406.2014.931780
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hole Accumulation and Deterioration of Device Performance in Polymer Solar Cells as Investigated by Light-Induced Electron Spin Resonance

Abstract: Light-induced electron spin resonance (LESR) study of polymer solar cells has been performed to investigate accumulated hole carriers in these devices under device operation. We analyzed clear correlation between the number of accumulated holes in regioregular poly(3-hexylthiophene) (P3HT) evaluated by LESR and the deterioration of device performance (V oc , J sc ) observed using the same device under simulated solar irradiation. The effects of hole accumulation with deep trapping levels formed in P3HTat the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…We now turn to a discussion of the mechanism which has deteriorated the device performance. When charges are accumulated in cells, the short-circuit current density is described as a function of N spin as follows , Here, e is elementary charge, N is charge density, μ is the mobility of Matthiessen’s rule, E is internal electric field, μ SC is the mobility without charge accumulation, μ CA is the mobility with charge accumulation, and c is a proportional constant. From eq , we obtain J (0) = Neμ SC E , which gives J SC ( N spin )/ J SC (0) as follows: From eq , we can know that the J SC decreases as the N spin increases because the collision time decreases due to the charge-carrier scattering by accumulated charges.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We now turn to a discussion of the mechanism which has deteriorated the device performance. When charges are accumulated in cells, the short-circuit current density is described as a function of N spin as follows , Here, e is elementary charge, N is charge density, μ is the mobility of Matthiessen’s rule, E is internal electric field, μ SC is the mobility without charge accumulation, μ CA is the mobility with charge accumulation, and c is a proportional constant. From eq , we obtain J (0) = Neμ SC E , which gives J SC ( N spin )/ J SC (0) as follows: From eq , we can know that the J SC decreases as the N spin increases because the collision time decreases due to the charge-carrier scattering by accumulated charges.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We now turn to a discussion of the mechanism which has deteriorated the device performance. When charges are accumulated in cells, the short-circuit current density is described as a function of Nspin as follows: 36,37…”
Section: Deterioration Mechanism Of Ptzntz Solar Cellsmentioning
confidence: 99%
“…2c, the J SC of the cell rapidly decreased (see the inset) and then gradually increased (see the main panel) when the N spin increased under short-circuit conditions. The studies of organic solar cells have reported the J SC decrease due to charge-carrier scatterings by charge accumulation in cells 22,33,34 . When the charge-carrier scatterings occur due to hole accumulation or formation, the current density j of a solar cell may be described with a following equation based on the Matthiessen's rule with charge density (n), electric elemental quantity (e), charge mobility (μ) in the cell, internal electric field (E), charge mobility before (μ SC ), and after hole accumulation (μ HA ), and a proportional constant (c) 33,34 :…”
Section: Resultsmentioning
confidence: 99%
“…2d, the V OC decreased as the hole accumulation increased. The studies of organic solar cells have discussed that when hole accumulation occurs in p-type polymers at the interfaces between photoactive and hole-transport layers, a vacuum-level shift occurs and decreases the V OC 22,33,37 . In this study, it is expected that the V OC decrease is influenced by the shift of the vacuum level owing to accumulated holes at the interfaces between spiro-OMeTAD and gold electrode, because the perovskite layer has no charge accumulation and the electron accumulation in the metallic gold electrode may be unobservable due to the Pauli paramagnetism and the ESR detection limit as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation